2015
DOI: 10.5301/jva.5000459
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Arteriovenous Fistula Failure after First Radiologic Intervention

Abstract: The location and size of the AVF stenosis at first PTA appear to be consistent factors associated with worse postintervention primary patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
4
15
2
3
Order By: Relevance
“…Interestingly, Manninen et al showed that age of fistula Brescia Cimino at the time of first angioplasty does not affect the result and that the most important predicting factors for future restenosis are the site of stenosis and the existence of stenosis in the region of anastomosis or in a small diameter vessel [ 34 ]. In another study, it is reported that stenosis of length greater than 2 cm is also a predisposing factor for restenosis after angioplasty [ 35 ].…”
Section: Primary and Secondary Patency After Ptamentioning
confidence: 99%
“…Interestingly, Manninen et al showed that age of fistula Brescia Cimino at the time of first angioplasty does not affect the result and that the most important predicting factors for future restenosis are the site of stenosis and the existence of stenosis in the region of anastomosis or in a small diameter vessel [ 34 ]. In another study, it is reported that stenosis of length greater than 2 cm is also a predisposing factor for restenosis after angioplasty [ 35 ].…”
Section: Primary and Secondary Patency After Ptamentioning
confidence: 99%
“…In addition, the patency rates of all cases of occlusion treatment as well as those of cases using biopsy forceps were superior. 1317 It is considered that the appropriate selection of treatment improved the overall patency rate of the occlusion cases. It is important to determine which cases of occlusion endovascular treatment or surgical revascularization will be suitable for the appropriate use of biopsy forceps.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of prior investigations, recurrent dysfunction of AVF within 6 months after initial PTA was seen in more than 25% of cases and most cases were recurrent stenosis [25]. Of note, AVF dysfunction is one of the leading causes of morbidity and mortality in hemodialysis patients and is responsible for their high percentage of hospitalizations [5].…”
Section: Discussionmentioning
confidence: 99%